Tantangan dan Inovasi Klasifikasi Warna untuk Aksesibilitas Pemustaka Buta Warna - Ferisa Efrilia; Marlini Marlini (KAMPUS AKADEMIK PUBLISING, 2026)
One visual innovation widely applied in library collection management and information retrieval programs is color classification, which can accelerate the search and navigation of library materials. This study aims to examine the challenges and innovations of color classification in enhancing accessibility for color-blind users in library environments. A qualitative descriptive approach was employed in this research, using a literature review method that analyzed national and international scholarly sources published between 2015 and 2020. The findings indicate that the use of color as the primary classification marker without supporting alternative elements can hinder collection retrieval, spatial navigation, and the independence of color-blind users. In addition, the absence of inclusive design standards and limitations in technical regulations are identified as the two main barriers to implementing accessible color classification systems. This study identifies several inclusive innovations, including the integration of text, visual symbols, high-contrast color schemes, QR codes, and the application of universal design principles in library classification and navigation systems. The study concludes that the development of inclusive color classification not only improves accessibility for color-blind users but also enhances service quality and strengthens the image of libraries as equitable, disability-friendly, and user-centered information institutions.